PROFIL PENGETAHUAN DAN HAMBATAN TERHADAP INSULIN PADA PASIEN DIABETES MELITUS TIPE 2 DI RUMAH DIABETES UBAYA - I Komang Kurnia Putra S.; Lisa Aditama (CALYPTRA, 2018)
This study was conducted to determine the level knowledge and berriers of patients with type 2 diabetes to insulin. This study uses non-experimental mixed methods (observational) method and cross sectional data collection technique in patients with type 2 diabetes using insulin, administered by Rumah Diabetes UBAYA. Tools or instruments used in this study are questionnaires and interviews and sampling on this research using purposive sampling method. Total subjects in getting as many as 30 people with the results of research 4 subjects get a total score of > 81% where knowledge of good insulin, 20 subjects get a total percentage score of 60% - 80% where the knowledge of insulin from the subject is normal, and 6 subjects get a percentage total score of <60% which is said knowledge of subject to insulin still less. And the average subject does not barriers about insulin, only a few have barrires of insulin.